THERMAL MANAGEMENT OF LITHIUM-ION BATTERY PACKS BY USING CORRUGATED CHANNELS WITH NANO-ENHANCED COOLING - Selimefendigil, Fatih; Can, Aykut; Öztop, Hakan Fehmi (Begell House Inc, 2024)
In this study, a cooling system using corrugated cooling channels and Al2O3 -Cu/water hybrid nanofluid is offered as the battery thermal management system (BTMS) for prismatic Li -ion batteries. A computational model built based on the finite element approach uses hybrid nanofluid at solid volume fractions ranging from 0 to 2% at various Reynolds numbers. The cold plates are corrugated and have a variety of square grooves positioned between prismatic Li -ion battery cells. The maximum temperature decreases as the volume fraction of solid nanoparticles and the number of corrugated cooling channels increases. When cases of using lowest and highest number of cooling channels are compared, maximum temperature reduction is found as 3.07 K when using water and 1.86 K when using Al2O3 -Cu/ water hybrid nanofluid (at the largest solid volume fraction). The number of square grooves in the cooling channels does not have any significant impact on the temperature drop when using nanofluid at the highest solid volume fraction.
Keywords: battery thermal management system; number of channel; number of grooves; finite element method; hybrid nanofluid